The inheritors an extravagant story ; The nature of a crime - Conrad, Joseph 1857-1924; Ford, Ford Madox 1873-1939 (Cambridge University Press, 2022)
This volume offers scholars the first authoritative text of two works produced collaboratively by two of the most important modern British novelists. Long hard to obtain and frequently neglected by critics, each can now be appreciated both in its own right and as part of the two authors' individual oeuvres. This scholarly edition situates both works in the context of the writers' meeting and ongoing collaboration, providing illuminating literary and historical references and detailing the works' composition history and reception in the UK and America. As well as establishing definitive texts of both works and of the authors' prefaces written for the 1924 republication of The Nature of a Crime, this edition also includes Ford's own 1924 account of his collaboration with Conrad on The Inheritors, as well as the text of Ford's 'The Old Story', a hitherto unpublished early draft of the basic plot of The Nature of a Crime